Zbirka portreta iz fundusa Kneževa dvora : muzejska prezentacija, podrijetlo i putovi nabave : doktorski rad = The portrait collection from the holdings of the Rector's palace : museum presentation, provenance and acquisition : doctoral thesis - Gjukić-Bender, Vedrana (V. Gjukić-Bender, 2012)
Sažetak/ Summary